Vitamin D Levels Aptly Sustained Insulin Resistance Markers - Farkad K. Ismail; Mohammed KJ Alnori; Mohammed A. Ajeel; Azlina A. Razak (University of Mosul, 2024)
Background: Insulin resistance is the underlying etiology for a variety of metabolic diseases including metabolic syndrome, type 2 diabetes, and obesity, alongside with their complication. The insulin resistance mechanism is complex and yet obscure. Vitamin D is a fundamental parameter involved in various ailments. We aimed to identify the link between vitamin D levels and glycemic/lipid parameters using patients with different metabolic diseases as a model. Methods: Serum samples were collected from patients with diabetes (n=20), metabolic syndrome (n=20), and obesity (n=15) versus the control group (n=18) with matched age, sex, and health status. Vitamin D and insulin were quantified by colorimetric technique and the total cholesterol (TC), triglyceride (TG), high density-lipoprotein (HDL) were measured in the studied groups using standard kits. Low density-lipoprotein (LDL), very low-density lipoprotein, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were calculated using standard formula. Results: The study found that insulin and vitamin D levels were significantly lower in diabetic [18.7±2.2, 16.5±4.4], metabolic syndrome [23.6±1.6, 18.6±3.4], and obese patients [15±1.9, 14.1±4.8] compared to the control group [9.8±4, 25±5.1]. Serum TC levels were higher in metabolic syndrome and obese subjects compared to control and diabetic subjects, TG levels were significantly higher in metabolic syndrome compared to the other groups, HDL levels were reduced in diabetic, metabolic syndrome, and obese groups compared to the control group, LDL levels were elevated in metabolic syndrome and obese groups compared to diabetic and control groups, VLDL levels were significantly higher in metabolic syndrome than in other groups. Conclusion: Vitamin D reduced in metabolic diseases reciprocally aligned with insulin level and associated with variation in lipid parameters.